Respuesta :

Answer:

f(x)=3x-2

g(x)=x^2

(g o f)(3)=?

(g o f)(3)=g(f(3))

x=3→f(3)=3(3)-2

f(3)=9-2

f(3)=7

(g o f)(3)=g(f(3))=g(7)

x=7→g(7)=7^2

g(7)=49

Answer: (g o f)(3)=49

OR,if you like this answer can also work

For this case, the first thing we must do is the composition of functions.

We have:

f (x) = 3x-2

g (x) = x ^ 2

(gOf) (x) = (3x-2) ^ 2

We now evaluate the function:

(gOf) (3) = (3 * (3) -2) ^ 2

(gOf) (3) = (9-2) ^ 2

(gOf) (3) = (7) ^ 2

(gOf) (3) = 49

Answer:

(gOf) (3) = 49

Both are same

Hope it is helpful to you